2020
DOI: 10.1186/s12885-020-07436-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and clinicopathological characteristics of C1RL in 2120 glioma patients

Abstract: Background Glioma is a deadly and immunosuppressive brain tumour. Complement C1r subcomponent like (C1RL), a prognostic biomarker in several kinds of tumours, has attracted increasing attention from oncologists. However, the role of C1RL in glioma remains unclear. Methods Through analysis of 2120 glioma patients from 5 public datasets, the relationships between C1RL expression and clinicopathological characteristics were evaluated. Furthermore, the C1RL-associated genes were screened, and Gene Ontology (GO) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Among the DEPs, the protein products of the genes C1RL, NID1, FN1, and PCYOX were upregulated in NT1. C1RL was previously found to be involved in immunological activities and reported as an independent prognostic biomarker in glioblastoma (GBM); interestingly, C1RL was also found to be upregulated (in GBM) in the study [ 40 , 41 ]. FN1 is a gene commonly reported in gene expression studies related to cancer and neurodegenerative diseases [ 19 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 92%
“…Among the DEPs, the protein products of the genes C1RL, NID1, FN1, and PCYOX were upregulated in NT1. C1RL was previously found to be involved in immunological activities and reported as an independent prognostic biomarker in glioblastoma (GBM); interestingly, C1RL was also found to be upregulated (in GBM) in the study [ 40 , 41 ]. FN1 is a gene commonly reported in gene expression studies related to cancer and neurodegenerative diseases [ 19 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 92%
“…A study found higher levels of C1Q expression were correlated with unfavorable prognosis in LGG ( 63 ). Other studies suggested that C3 and C1RL can serve as diagnostic biomarkers and potential targets of therapy for LGG patients ( 78 , 79 ). On the other hand, TF is related to epithelial-mesenchymal transition (EMT) and has the potential to become an effective target against EMT and thrombotic events in LGG.…”
Section: Discussionmentioning
confidence: 99%
“…The p values of significant glycopeptides are shown in Table 2. The protein sources of significant glycopeptides were already reportedly involved in immunological activities, cancer, and neurodegenerative disease [43,55]. Inter-alpha-trypsin inhibitor H4, complement factor B, ceruloplasmin, fibronectin, and prothrombin were among the significant glycoproteins that were identified in the 28 significant glycopeptides.…”
Section: Discussionmentioning
confidence: 99%